2004
DOI: 10.1063/1.1689664
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure measurements of dense plasmas

Abstract: This paper presents an improved analytical expression for the x-ray dynamic structure factor from a dense plasma which includes the effects of weakly bound electrons. This result can be applied to describe scattering from low to moderate Z plasmas, and it covers the entire range of plasma conditions that can be found in inertial confinement fusion experiments, from ideal to degenerate up to moderately coupled systems. The theory is used to interpret x-ray scattering experiments from solid density carbon plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…These electrons become available for inelastic scattering by x rays and contribute to the Compton feature by excitation and ionization. The intensity ratio of the inelastic Compton to the elastic Rayleigh scattering component can hence be a sensitive measure of the ionization state [18,19]. In isochorically heated matter where the ion density is known a priori, the ionization state also provides a measurement of the electron density.…”
mentioning
confidence: 99%
“…These electrons become available for inelastic scattering by x rays and contribute to the Compton feature by excitation and ionization. The intensity ratio of the inelastic Compton to the elastic Rayleigh scattering component can hence be a sensitive measure of the ionization state [18,19]. In isochorically heated matter where the ion density is known a priori, the ionization state also provides a measurement of the electron density.…”
mentioning
confidence: 99%
“…The effort to characterize under-dense and solid-density plasmas with optical and x-ray scattering, respectively, is well established [32,33,48,49,50,51]. Temperature, density, and ionization state measurements have been demonstrated in isochorically-heated solid-density plasmas using non-collective backward scattering [29] and are presently applied in numerous plasmas with a significant amount of ionization [37].…”
Section: B) Current Statusmentioning
confidence: 99%
“…At the moment, the VUV-FEL at DESY Hamburg operates at 32 nm wavelength [11], corresponding to 38 eV photons. With this coherent light source, dense matter up to solid densities of 10 23 cm −3 can be penetrated, see Refs. [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Glenzer et al [8,9] have shown and explored the possibility of x-ray Thomson scattering in solid density targets using the Ti He-α line at 4.75 keV as probe light [10]. A new alternative emerged with the development of VUV-free electron lasers (VUV-FEL), providing pulses of coherent radiation in the far (vacuum-) ultraviolet.…”
Section: Introductionmentioning
confidence: 99%